Teh Temujahecang Sebagai Produk Inovatif Untuk Meningkatkan Kesehatan Masyarakat - Sisilia Rosmala Dewi; Rusdiaman Rusdiaman; Santi Sinala; Sainal Edi Kamal; Zulfiayu Sapiun (Jurusan Farmasi Politeknik Kesehatan Makassar, 2022)
“Temujahecang tea” is a drink that warms the body and the ingredients are from aromatic plants such as salvia leaves, temulawak, ginger, secang, cardamom, lemongrass leaves, cinnamon and mint leaves as flavorings in the drink. This tea has nutritious ingredients that have been proven to be beneficial for health, and herbal ingredients are now starting to be sought after by many people to restore health, especially in disease prevention. The results of several studies / studies show that the ingredients in this drink can prevent and reduce / minimize the occurrence of chronic diseases commonly experienced by the elderly / degenerative diseases, namely antioxidants, lowering cholesterol, preventing osteoporosis, anti-diarrhea, anti-cancer, so that people who drink this tea can improve health. Therefore we need an innovation to overcome this problem, namely making